The Study of Gas Powered Automatic Satay Grill Machine - MOHD SHARIF, MUHAMMAD HASIF YUSUF; Yusof, Mohd Sallehuddin (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The present study focuses on the design, development, and performance evaluation of a gas-powered automatic satay grill machine for commercial food service applications. Satay, a popular Southeast Asian dish, involves grilling marinated meat skewers over an open flame. Traditionally, this process has been labor-intensive and time-consuming, posing challenges for high-volume food establishments. The objective of this project was to engineer an automated satay grill machine that can improve productivity and consistency in satay preparation, while maintaining the authentic charcoal-grilled flavor profile. The key design considerations included an efficient gas-powered heating system, a motorized skewer rotation mechanism, and intuitive control interfaces to streamline the grilling process. Through a systematic approach involving thermodynamic analysis, structural simulations, and prototype testing, an optimized gas-powered automatic satay grill machine was developed. The final design incorporates features such as adjustable heat zones, automated skewer rotation, and digital temperature monitoring to enable precise control over the grilling parameters. Performance evaluations demonstrated the machine’s ability to consistently produce high-quality satay with reduced labor requirements and improved throughput compared to manual methods. The findings of this study suggest that the developed gas-powered automatic satay grill machine can serve as a valuable asset for commercial kitchens, enabling them to meet the growing demand for authentic satay dishes while enhancing operational efficiency. The insights gained from this project can also inform the design of similar automated food preparation systems for other traditional grilled delicacies.